2022
DOI: 10.3390/cells11244073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Stress on Bovine Oocytes and Early Embryonic Development—An Update

Abstract: Heat stress is a major threat to cattle reproduction today. It has been shown that the effect of high temperature not only has a negative effect on the hormonal balance, but also directly affects the quality of oocytes, disrupting the function of mitochondria, fragmenting their DNA and changing their maternal transcription. Studies suggest that the induction of HSP70 may reduce the apoptosis of granular layer cells caused by heat stress. It has been shown that the changes at the transcriptome level caused by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…Summer heat stress disrupts homeostatic reproduction in cattle by affecting fertility and reproductive function [19]. Extensive in vitro studies indicate that 12 h of heat stress (41 • C) during early maturation dramatically reduces COC viability and blastocyst production [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Summer heat stress disrupts homeostatic reproduction in cattle by affecting fertility and reproductive function [19]. Extensive in vitro studies indicate that 12 h of heat stress (41 • C) during early maturation dramatically reduces COC viability and blastocyst production [28].…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress has been linked to epigenetic modifications that adversely affect the growth and development of bovine oocytes and embryos [18]. The dynamic changes in the epigenome are caused by the complex interaction of genetic and environmental factors [19]. They are considered very critical for normal dairy cattle oocyte development, particularly when exposed to heat stress [20].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Khan et al [ 47 ] reported that HS significantly compromises granulosa cells, leading to suboptimal oocyte development. This is further supported by studies that found HS compromises the mRNA expression levels of Moloney sarcoma oncogene (MOS), growth factor 9 (GDF9), and POU domain, class 5, transcription factor 1 (POUF51), which are crucial for oocyte development and competence, ultimately resulting in poor-quality oocytes and impaired embryonic development [ 60 , 61 , 70 , 71 , 72 ]. Figure 1 demonstrates the adverse impact of heat stress on phenotypic traits related to mammalian reproductive traits.…”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, HS exerts detrimental effects on follicle quality and hormonal equilibrium, contributing to a decline in estrus [ 54 , 55 , 56 , 57 , 58 ]. Specifically, granulosa cells responsible for estradiol production are adversely affected by HS, resulting in decreased estradiol production and subsequent disruption of the estrous cycle in cattle [ 59 , 60 , 61 ]. HS has also been shown to influence corticoid levels, luteinizing hormone (LH), and plasma progesterone in cattle, with alterations in hypothalamus and pituitary gland function leading to changes in the secretion of reproductive hormones [ 9 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthy adult cows maintain a body temperature of 38.4–39.1 °C in thermoneutral zones, i.e., in the range of outdoor temperatures of 4–16 °C [ 10 ]. Above these temperature indications, i.e., above 25 °C, an increase in body temperature is observed in cattle, which results in heat stress [ 8 , 11 , 12 ]. Moreover, heat stress has been shown to disrupt the production of steroid hormones, significantly alter the composition of the follicular fluid, and reduce granulosa cells (GCs), which are essential for developing oocyte competence in cows [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%